Bovine Viral Diarrhea Virus Core Is an Intrinsically Disordered Protein That Binds RNA - Murray, Catherine L. (American Society for Microbiology (ASM), 2008)
Pestiviruses, including bovine viral diarrhea virus (BVDV), are important animal pathogens and close relatives of hepatitis C virus. Pestivirus particles are composed of an RNA genome, a host-derived lipid envelope, and four virion-encoded structural proteins, core (C), E(rns), E1, and E2. Core is a small, highly basic polypeptide that is processed by three enzymatic cleavages before its incorporation into virions. Little is known about its biological properties or its role in virion assembly and structure. We have purified BVDV core protein and characterized it biochemically. We have determined that the processed form of core lacks significant secondary structure and is instead intrinsically disordered. Consistent with its highly basic sequence, we observed that core binds to RNA, although with low affinity and little discernible specificity. We found that BVDV core protein was able to functionally replace the nonspecific RNA binding and condensing region of an unrelated viral capsid protein. Together these results suggest that the in vitro properties of core may reflect its mechanism of action in RNA packaging and virion morphogenesis.